Model ARIAS berbasis TSTS terhadap Kemampuan Berpikir Kritis Matematis Ditinjau dari Gaya Kognitif - Desmawati, Desmawati; Farida, Farida (Desimal: Jurnal Matematika, 2018)
This study aims to determine whether there is the influence of ARIAS model based on Two Stay Two Stray model to critical thinking ability mathematically. This research is Quasi-Experimental Design research. Hypothesis testing using variance analysis of two different cell roads Based on the test of cell variance analysis is not the same obtained that there is influence of ARIAS model based on Two Stay Two Stray to critical mathematical thinking ability and there is influence of cognitive style to critical thinking skill mathematically, where student with treatment of learning using integrated learning model ARIAS TSTS learning model on the ability of critical thinking is better than students with learning treatment using lecture methods in terms of each student's cognitive style. The students' mathematical critical thinking ability with independent field cognitive style is better than students with cognitive field dependent style. There is no interaction between learning and cognitive styles to critical mathematical thinking skills.